2015
DOI: 10.1080/01431161.2014.1001085
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of cloud masking schemes for satellite ocean colour data of marine optical extremes

Abstract: One of the most important steps in utilizing ocean colour remote-sensing data is subtracting the contribution of the atmosphere from the signal at the satellite to obtain marine water-leaving radiance. To be carried out accurately, this requires clear-sky conditions, i.e. all clouds need to be excluded or masked from the data prior to atmospheric correction. The standard cloud mask used routinely in the processing of NASA global ocean colour data is based on a simple threshold applied to the Rayleigh-corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…ASTER band 3N reflectances R 0.86,A need to exceed distinct thresholds. Similar tests to identify clear-sky pixels have been reported by Ackerman et al (1998), Ackerman et al (2008), Frey et al (2008), and Banks and Mélin (2015) for MODIS observations, generally establishing thresholds of R 0.86,M < 0.03 for confidently clear and R 0.86,M > 0.065 for cloudy pixels.…”
Section: Cloud Detection For Astermentioning
confidence: 93%
See 1 more Smart Citation
“…ASTER band 3N reflectances R 0.86,A need to exceed distinct thresholds. Similar tests to identify clear-sky pixels have been reported by Ackerman et al (1998), Ackerman et al (2008), Frey et al (2008), and Banks and Mélin (2015) for MODIS observations, generally establishing thresholds of R 0.86,M < 0.03 for confidently clear and R 0.86,M > 0.065 for cloudy pixels.…”
Section: Cloud Detection For Astermentioning
confidence: 93%
“…This ratio utilizes the rather constant spectral behavior of clouds in the VNIR, which leads to their white appearance. Ackerman et al (1998) found thresholds of 0.8 < r 1 < 1.1, while Ackerman et al (2008) and Banks and Mélin (2015) reported adjusted lower thresholds of 0.85 and 0.95 for confidently clear and cloudy pixels, respectively. The upper threshold is usually set to 1.1, in part to exclude land surfaces.…”
Section: Cloud Detection For Astermentioning
confidence: 99%
“…2 Satellite AAC retrieval algorithm summary and updates 2.1 Relevant sensor characteristics Sayer et al (2016) developed the AAC retrieval algorithm with a goal of implementation being as similar as feasible across the different sensors, relying on only those bands common to the three instrument types. SeaWiFS (McClain et al, 2004), MODIS (Barnes et al, 1998), and VIIRS (Cao et al, 2013) are all passive broad-swath imaging radiometers. Sea-WiFS operated from late 1997 to December 2010; MODIS provides data on the Terra platform from late February 2000, MODIS on the Aqua platform from July 2002, and VIIRS on the Suomi National Polar-orbiting Partnership (SNPP) from March 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite monitoring provides an essential part of this global observing network but also requires a comprehensive global network of trustworthy and accurate in situ measurements for validation and calibration. The present reality is that the actual sampling of a number of important climate-related variables, including temperature, is unevenly distributed in space or time with a large part of the coastal regions being poorly sampled [18][19][20].…”
Section: Introductionmentioning
confidence: 99%